Assessing the Prospects for an E.U.-ASEAN Air Transport Agreement - Khee, Alan (International Transport Forum Discussion Papers, 2015)
In February 2014, transport officials from the European Union (E.U.) and the Association of Southeast Asian Nations (ASEAN) met on the sidelines of the Singapore Airshow to discuss a possible comprehensive air transport agreement between both sides. At the meeting's conclusion, the ASEAN states invited the European Commission to launch the internal processes necessary to secure a mandate to commence negotiations on an agreement. In particular, ASEAN welcomed Vice President of the European Commission and Commissioner for Transport Siim Kallas' statement that he would propose to the Commission to seek authorization from the Council of the European Union to start negotiations (E.U.-ASEAN Joint Declaration, 2014)